IDENTIFIKASI KEPUTUSAN PEMBELIAN PADA APLIKASI MARKETPLACE DI MASA PANDEMI COVID-19 MELALUI ONLINE CUSTOMER REVIEW, ONLINE CUSTOMER RATING DAN ONLINE VLOGGER REVIEW - Sulasih Sulasih; Weni Novandari; Suliyanto Suliyanto; Anggita Syafni Aulia (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2021)
The purpose is to identify purchasing decisions on marketplace applications during the Covid 19 pandemic through online customer reviews, online customer ratings and online vlogger reviews. This type of research is quantitative with purposive sampling and accidental sampling techniques and multiple linear regression data analysis techniques. The results of this study indicate that online customer review (X1) has a positive influence on purchasing decisions. Where online customer review (X1) can be used as a benchmark for respondents to make purchasing decisions. In addition, online customer rating (X2) has a positive influence on purchasing decisions. Where online customer rating (X2) can be used as a benchmark for respondents to make purchasing decisions. The online vlogger review variable (X3) has a positive influence on purchasing decisions. Where online vlogger review (X3) can be used as a benchmark for respondents to make purchasing decisions. Simultaneously shows that the independent variables online customer review (X1), online customer rating (X2) and online vlogger review (X3) affect the dependent variable on purchasing decisions (Y) on marketplace applications during the Covid-19 pandemic.